Na pomoc casné diagnostice hypotalamo-hypofyzárního nanismu: prirozený růst dĕtí s deficitem růstového hormonu v prvních letech zivota - Lebl, J; Zemková, D (Ceskoslovenska pediatrie, 1990)
In order to assess when and on the basis of which developmental parameters it is possible for the community paediatrician to express suspicion of growth hormone deficiency in a child, the authors analyzed anamnestic perinatal and postnatal parameters up to the age of 3 years in 47 children (31 boys, 16 girls), where during subsequent life the classical form of so-called idiopathic growth hormone deficiency (hypothalamo-hypophyseal nanism) was diagnosed. The ratio of breech presentations and other deliveries was 13:18 in the affected boys and 1:15 in the girls. In children delivered by vertex presentation or section we may consider, using the criterion of -2 SD height, a deficit of growth hormone in 67% (boys) and 57% (girls) already at the age of 6 months, and in 88% and 79% resp. at the age of 3 years when the growth retardation is associated only with a minor degree of body weight retardation. In boys delivered by breech presentation growth retardation occurs later. Their development in the first year of life is usually unconspicuous, only at the age of 3 years in 70% growth becomes retarded by more than 2 SD.
Keywords: Growth Hormone; kojenec; Time Factors; mužské pohlaví; Infant; hypofyzární nanismus; růst; Child, Preschool; referenční hodnoty; ženské pohlaví; Growth; Humans; předškolní dítě; Reference Values; časové faktory; růstový hormon; Female; lidé; Male; Dwarfism, Pituitary